Prediction and experimental validation of temperature rise in ductile mode end milling of soda-lime glass - Bagum, Mst. Nasima; Konneh, Mohamed; Amin, A. K. M. Nurul (Springer London, 2018)
The suitable thermal, chemical, and corrosion resistance properties of glass make it possible to be used in a wide variety of product manufacturing, like lenses, mirrors, mold, semiconductor, biomedical, optical, and micro-electronics. However, machining of glass like any brittle material has big challenges owing to its inherent brittleness. Ductile mode machining is known to promote the material removal from a brittle material in ductile manner rather than by brittle fracture. In high-speed machining, the thermal softening effects can enhance flexibility in ductile machining of brittle materials. In this paper, an analytical model is developed to predict the amount of temperature generated in the immediate next removable layer (INRL) of the soda-lime glass work piece per unit depth of cut ∆T¯ INRL based on fundamental micro-machining principle and material physical properties. The model incorporates the effects of cutting speed, feed rate, strain rate, and thermal softening effect. The simulation and experimental results showed that at high cutting speed, glass softening can be achieved by adiabatic heating in order to facilitate ductile machining. The amount of adiabatic heating can be controlled by predicting the amount of the ∆T¯ INRL.